Risk stratification for ventricular arrhythmias and sudden cardiac death in arrhythmogenic right ventricular cardiomyopathy: an update. (2nd September 2019) - Cadrin-Tourigny, Julia; Bosman, Laurens P; Tadros, Rafik; Talajic, Mario; Rivard, Lena; James, Cynthia A; Khairy, Paul
ABSTRACT: Introduction : Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetically determined disease associated with a significant risk of ventricular arrhythmias and sudden cardiac death (SCD). Implantable cardioverter-defibrillators (ICDs) are the only effective preventive measure. Over the past 30 years, much effort has been invested in determining predictors of adverse arrhythmic events in these patients. Areas covered : This review summarizes available evidence on risk stratification for ARVC, with an emphasis on recent research findings. While efforts are ongoing to define risk predictors, several recent publications have synthetized and built on this knowledge base. A recently published meta-analysis has clarified the strongest predictors of ventricular arrhythmias in ARVC, which vary depending on the population included. Three management guidelines/expert consensus documents have integrated the previously described risk predictors into proposed ICD recommendations. Furthermore, a risk prediction model has allowed the integration of multiple risk factors to provide individualized risk prediction and to inform shared-decision making regarding ICD implantation. Expert opinion : Over the past few years, knowledge of risk prediction in ARVC has been consolidated and refined. Further improvements may be made by the considering additional predictors such as exercise and by targeting more specific surrogate outcomes for SCD.